A review of parabolic collector with shell and tube heat exchanger. (2022) - Selvanayagam, Benjamin Franklin; S., Krishnamoorthy; S., Gowtham; N., Balaji
Abstract: The ever-increasing global need for energy makes it unavoidable to support the use of essential coffers (box or cabin). The sun is one of the most abundant and almost indestructible energy sources in our world. The goal of this study is to compare three alternative materials in order to improve or maximize the efficiency and other characteristics of the solar collector. Aluminum- 6061, Stainless Steel – 304 and Mild Steel - EN24 are the three materials. Solar collectors with a parabolic trough are physical devices with an interior covering of mirrors or reflecting materials. The collector is shaped like a concave surface. These troughs have a single axis, which means they may be rotated. These troughs have a single axis, which means they can only rotate in one direction. The east–west orientation is the most common and typical direction for solar collector placement. These collectors are also used in the north–south direction in various parts of the world and by some homes. The incident radiation on the collector heats a specific fluid as it flows through the tubes or pipes of the collector. Because they are in the shape of a parabola, solar collectors are also known as parabolic trough collectors. Despite the fact that the interior surface is coated with reflecting materials, mirrors are still used. The collector's form aids in the focus of falling light or radiation on the tubes. The shape of conventional solar collectors and parabolic solar collectors is what distinguishes them. One of the solar collector's most important qualities is this distinction. Mechanical and geometrical characteristics are among them. This reduces, if not completely eliminates, losses in the collection. These characteristics enable solar collectors to work at higher temperatures.